VEGFR-1/Flt-1 inhibition increases angiogenesis and improves muscle function in a mouse model of Duchenne muscular dystrophy - Jennifer Bosco; Zhiwei Zhou; Sofie Gabriëls; Mayank Verma; Nan Liu; Brian K. Miller; Sheng Gu; Dianna M. Lundberg; Yan Huang; Eilish Brown; Serene Josiah; Muthuraman Meiyappan; et al. (Molecular Therapy: Methods & Clinical Development, 2021)
Duchenne muscular dystrophy is characterized by structural degeneration of muscle, which is exacerbated by localized functional ischemia due to loss of nitric oxide synthase-induced vasodilation. Treatment strategies aimed at increasing vascular perfusion have been proposed. Toward this end, we have developed monoclonal antibodies (mAbs) that bind to the vascular endothelial growth factor (VEGF) receptor VEGFR-1 (Flt-1) and its soluble splice variant isoform (sFlt-1) leading to increased levels of free VEGF and proangiogenic signaling. The lead chimeric mAb, 21B3, had high affinity and specificity for both human and mouse sFlt-1 and inhibited VEGF binding to sFlt-1 in a competitive manner. Proof-of-concept studies in the mdx mouse model of Duchenne muscular dystrophy showed that intravenous administration of 21B3 led to elevated VEGF levels, increased vascularization and blood flow to muscles, and decreased fibrosis after 6–12 weeks of treatment. Greater muscle strength was also observed after 4 weeks of treatment. A humanized form of the mAb, 27H6, was engineered and demonstrated a comparable pharmacologic effect. Overall, administration of anti-Flt-1 mAbs in mdx mice inhibited the VEGF:Flt-1 interaction, promoted angiogenesis, and improved muscle function. These studies suggest a potential therapeutic benefit of Flt-1 inhibition for patients with Duchenne muscular dystrophy.